Centralised versus outreach models of cystic fibrosis care should be tailored to the needs of the individual patient. Issue 2 (9th February 2020) - Geake, James; Ballard, Emma; O'Rourke, Peter; Wainwright, Claire E.; Reid, David W.; Bell, Scott C.
Abstract: Cystic fibrosis (CF) is a common life‐limiting genetic condition. As the disease progresses access to specialist tertiary multi‐disciplinary care services may become necessary. For patients living in regional/remote Australia, accessing such services may be a challenge. Here, we describe long‐term outcomes for CF patients according to their access to specialist CF centre care in childhood.